1988
DOI: 10.1038/bjc.1988.192
|View full text |Cite
|
Sign up to set email alerts
|

A regression analysis of prognostic factors after resection of Dukes' B and C carcinoma of the rectum and rectosigmoid. Does post-operative radiotherapy change the prognosis?

Abstract: Summary The prognostic value of several clinical and histopathological characteristics has been evaluated in patients with Dukes' B and C carcinoma of the rectum and the rectosigmoid. Data on 260 Dukes' B and 208 Dukes' C tumours entered into a prospective, randomized clinical trial of post-operative radiotherapy (5OGy given with 2Gy/fraction in an overall time of 7 weeks) were analyzed by means of the Cox proportional hazards model. The Dukes' stages B and C were analyzed in two separate multivariate analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…However, there is also considerable variation in prognosis within the Dukes' stages (Newland et al, 1987;Lindmark et al, 1994). Bentzen et al (1988) showed, for example, that some subgroups of Dukes' stage C patients had better prognosis than some subgroups of Dukes' stage B patients. For therapeutic and surveillance reasons, it is of importance to find stronger prognostic factors other than the original Dukes' classification, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also considerable variation in prognosis within the Dukes' stages (Newland et al, 1987;Lindmark et al, 1994). Bentzen et al (1988) showed, for example, that some subgroups of Dukes' stage C patients had better prognosis than some subgroups of Dukes' stage B patients. For therapeutic and surveillance reasons, it is of importance to find stronger prognostic factors other than the original Dukes' classification, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Age, gender, TNM stage, venous invasion, tumour necrosis, peri-tumoural lymphocytic infiltration, tumour budding and CEA levels were also independently associated with poor survival in at least some studies [17,18,21,22,26,30,32,33,39].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 494 patients were randomised in a multicenter study (Balslev et al, 1982;Balslev et al, 1986;Bentzen et al, 1988a) of the effect of postoperative adjuvant radiotherapy after resection of Dukes' B and C colorectal cancer. The study was open for patient intake from September 1979 to March 1984 (Dukes' B) or March 1985 (Dukes' C). Staging was performed according to Dukes' classification (Dukes & Bussey, 1958), with B tumours defined as having penetrated the bowel wall completely, and C tumours as having regional lymph node metastases regardless of the degree of bowel-wall penetration.…”
Section: Methodsmentioning
confidence: 99%
“…Several randomised (Balslev et al, 1982;Gastrointestinal Tumor Study Group, 1985;Fisher et al, 1988) or historically-controlled clinical trials (Tepper et al, 1987;Vigliotti et al, 1987;Mohiuddin et al, 1985) have been concerned with the possible benefit from adjuvant post-operative radiotherapy in this disease. With respect to survival all have come out negative (Bentzen et al, 1988a;Douglass et al, 1986;Fisher et al, 1988): postoperative radiotherapy has not improved survival significantly even when quite substantial numbers of patients are compared. With respect to loco-regional control or disease-free survival diverse conclusions have been reached: in the NSABP study R-01 there was an overall reduction in loco-regional recurrence from 25% to 16% (P = 0.06 (Fisher et al, 1988)), while the GITSG study found no significant reduction in the loco-regional recurrence rate after adjuvant radiotherapy (Gastrointestinal Tumour Study Group, 1985).…”
mentioning
confidence: 99%
See 1 more Smart Citation